Access to urban housing in peninsular Malaysia: Social and spatial distortion in a peripheral economy / Michael A. Johnstone - Michael, A. Johnstone (1979)
This study is concerned with examining the origin and development of the social and spatial inequalities in the provision of urban housing in Peninsular Malaysia. This is done within a theoretical framework which stresses the need to understand the forces that have moulded the Malaysian space economy. Conventional housing provision is analysed using data on the activities of private development firms, which like other modern capitalist activity, are spatially and structurally concentrated. The conventional sector builds mainly high cost dwellings which the urban poor cannot afford and, despite an increasing quantity of cheaper accommodation provided by the public sector, the bulk of the poor search for alternatives in the unconventional sector. Unconventional housing, built outside the formal regulation and standards of the modern sector, is found in most Malaysian cities, where it has evolved since the early 1900s. Despite the importance of unconventional housing in many cities, government policy has been concerned with its clearance and eradication and has been based on a misunderstanding of the processes inherent in the development of these shelter types. The third part of the study examines in detail the construction and acquisition of squatter dwellings and the manner in which low income families accumulate capital which is invested in the development and improvement of such housing. Although squatter settlements do permit such activities to occur, they are not a vehicle for socio-economic mobility for all low income households because of the constraints of the urban political economy.